(3fKjQ GdLeGf aj TYQ ef fXefi hEjGg GdReGfs - (3GHf GdCMeQ , ESeGYjd Hf jhSa Hf eMeO Hf fUQ GdNRQLj GdfUQj, CHh GdhdjO,J (B807 (3g` s
(3ChdgG (B:s
(3bGd ESeGYjd Hf GdCejQ CHj GdMLGL GdTgjQ HGdCMeQhHYO aEfg deG cGf GdTYQ ai VHW GdbhGai hGdChRGf s
(3BNQgG (B:s
(3hCfTOfi CjVkG dfaSg jeOMg hjUa bJd GdCSOjf jOjg hcGf GdSdWGf ehdYkG HbJd GdEShO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B329s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(3791) s
Keywords: (3GdCOHs